Utility of EEG in the diagnosis of Efavirenz neurotoxity in HIV positive patients at a South African tertiary hospital - Ssemmanda, Salvatore (Department of Medicine, 2024)
Background: Efavirenz (EFV) is a widely used antiretroviral medication in HIV treatment, primarily metabolized by cytochrome P450 CYP2B6, an enzyme whose loss of function polymorphisms have been associated with risk of EFV neurotoxicity. Patients with late onset efavirenz neurotoxicity syndrome (LENS) may present with encephalopathy, for which scalp EEG (sEEG) is indicated. Although a characteristic pattern of sEEGs waveforms in this deleterious condition has been suggested before, this has not been studied. Objective: The aim of this study was to investigate the utility of sEEG as a biomarker of LENS. Methods: We analysed a 5-year retrospective period of sEEGs performed at Groote Schuur Hospital (GSH) neuro-electrophysiology laboratory between June 1, 2016, and May 31, 2021. From these we selected 5319 sEEGs with a “Dysrhythmia grade II generalized” (Mayo Clinic, Lemieux et al) classification performed on patients whose referral indication for sEEG was either encephalopathy, efavirenz neurotoxicity, encephalitis, delirium, confusion, neurocognitive decline or subclinical seizures. Following several exclusions, the analysed cohort of 63 sEEGs comprised of 13 sEEGs from adult HIV positive patients with laboratory confirmed EFV neurotoxicity (plasma EFV levels of > 4 ug/mL) and 50 sEEGs as controls. These were presented to two qualified and experienced blinded sEEG interpreters instructed to record if a sEEG was typical for waveform features of EFV neurotoxicity or not, following a demonstration using representative sEEG samples from outside the study duration. All data were anonymized and secured on password protected computers for standard statistical analyses including measurement of inter rater agreement, reliability, and correlation. A p-value of less than 0.05 was considered for statistical significance. Results: Patients with EFV neurotoxicity had characteristic sEEG findings of diffuse, monomorphic, bisynchronous, high voltage, rhythmic 4 – 7 Hz theta frequency waveform runs. These were detectable by the blinded interpreters with significantly strong inter rater agreement (mean kappa statistic = 0.88, p < 0.001), strong positive correlation (Spearman correlation coefficient = 0.81, p < 0.001) and significantly strong inter rater reliability (intraclass correlation coefficient = 0.86, 95% CI 0.77 – 0.92, p < 0.001). Conclusion: Our observation adds knowledge to existing literature on EFV neurotoxicity, by describing a characteristic sEEG pattern in patients with LENS that is reliably detectable by qualified sEEG interpreters. This is in view of our observation that in a tertiary hospital with people referred with a clinical diagnosis of encephalopathy and other confusional states meeting clinical referral criteria described in this study, with a proven Dysrhythmia grade II generalized pattern on sEEG, certain sEEG criteria may distinguish HIV positive patients with LENS from other patients with the same grade of dysrhythmia on sEEG. This may support the timeous diagnosis of EFV neurotoxicity and facilitate the workup of encephalopathic patientson EFV. Our finding may be representative of an effect of EFV on the oscillatory and spike rhythms of the reticular thalamic nuclei. Further research using a larger number of patients, studying correlation between plasma EFV levels in patients with LENS and their sEEG characteristics is suggested as it may be an electrophysiological biomarker of disease severity.